1999
DOI: 10.1172/jci5628
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of the Fas-Fas ligand pathway in the development of pulmonary fibrosis

Abstract: The Fas ligand is predominantly expressed in activated T lymphocytes and is one of the major effector molecules of cytotoxic T lymphocytes and natural killer cells. Previously, we found excessive apoptosis of epithelial cells and infiltrating lymphocytes expressing Fas ligand mRNA in the lung tissue of bleomycin-induced pulmonary fibrosis in mice. Here we demonstrated that the administration of a soluble form of Fas antigen or anti-Fas ligand antibody prevented the development of this model and that lpr and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
221
0
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(238 citation statements)
references
References 32 publications
8
221
0
9
Order By: Relevance
“…), but we did not observe any evidence for T cell activation or any significant activation of apoptotic pathways. Although in animal models of pulmonary fibrosis the fibrotic response may depend on intact tumor necrosis factor ␣ or Fas signaling pathways (31)(32)(33)(34)(35), activation of these pathways was not apparent in this study.…”
Section: Discussionmentioning
confidence: 67%
“…), but we did not observe any evidence for T cell activation or any significant activation of apoptotic pathways. Although in animal models of pulmonary fibrosis the fibrotic response may depend on intact tumor necrosis factor ␣ or Fas signaling pathways (31)(32)(33)(34)(35), activation of these pathways was not apparent in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Bleomycin induces the expression of TNF receptors in mice (22). In an in vivo study, Fas-and FasLdeficient C3H mice (lpr/lpr and gld/gld) displayed reduced susceptibility to bleomycin-induced pulmonary fibrosis (16). However, in a subsequent study, Aoshiba et al (3) used lpr/lpr and gld/gld in the C57BL/6 murine strain and found no change in bleomycin-induced pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the extrinsic apoptotic pathway is essential in bleomycin model for lung injury and fibrosis (11,16). Bleomycin induces the expression of TNF receptors in mice (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in the regulation of apoptosis have been associated with several pulmonary diseases, including acute lung injury, 11,12 diffuse alveolar damage, 13 idiopathic pulmonary fibrosis, 14 and lung disorders caused by bleomycin, 15,16 silica, 17 endotoxin, 18 and the deposition of immune complexes. 19 Despite growing evidence for a role of apoptosis and lung surfactant in pulmonary disorders, the relationship between these two events is not well understood.…”
mentioning
confidence: 99%